Incorporating Participant Voice in Culturally Responsive Leadership: A Case Study. Issue 3 (2nd July 2020) - Levitan, Joseph
ABSTRACT: This article discusses the promises and complexities of culturally responsive leadership in schools. The study takes place in a rural secondary school in the Peruvian Andes using a participant voice methodology with 146 students and 50 parents. The goal of the study was to ascertain students' and parents' learning goals and aspirations to create responsive educational opportunities. Three major themes emerged from the study, each of which had implications for different theoretical orientations regarding education development. Findings suggest that culturally responsive leadership requires participant-voice practices, and that careful, multi-theory interpretation is necessary to understand participants in school contexts.